The analysis of tendencies of development of internet marketing in Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Now transition to information economy represents modification of the existing market system. The market economy is at that stage when the production criterion exists, but loses the importance. This thesis underlines a role of use of information technologies at the organization of marketing activity at the level of the state and the enterprise.Scientific novelty of research consists in identification of the main tendencies of development of internet marketing, definition of the problems existing now and ways of their decision.In article actors are considered, objects of property of the Internet market and are analysed forms of interaction between them at the present stage of development of information sector of economy of the Republic of Kazakhstan. As a result of the made analysis valid conclusions by results of research.
Keywords: internet marketing; information and communication tech nologies; information sector of economy; electronic government.